A nationwide survey of Leishmania infantum infection in cats and associated risk factors in Italy. - Roberta Iatta; Tommaso Furlanello; Vito Colella; Viviana Domenica Tarallo; Maria Stefania Latrofa; Emanuele Brianti; Paolo Trerotoli; Nicola Decaro; Eleonora Lorusso; Bettina Schunack; Guadalupe Mirò; Filipe Dantas-Torres; et al. (Public Library of Science (PLoS), 2019)
Though scantly investigated, Leishmania infantum infection and clinical cases of leishmaniasis in cats have been recently reported in several countries of the Mediterranean basin, with large variability in prevalence data. A major limitation in the comparability of the data available is attributed to the differences in diagnostic techniques employed and cat populations sampled. The aim of this study was to assess the prevalence of L. infantum infection in owned cats across Italy by serological and molecular tests and the identification of potential risk factors. Blood samples from 2,659 cats from northern (n = 1,543), central (n = 471) and southern (n = 645) Italy were tested for antibodies against L. infantum, by an immunofluorescence antibody test and for the parasites' DNA, by real-time PCR. Samples were additionally screened for feline leukemia virus (FeLV) and feline immunodeficiency virus (FIV) proviral DNAs. An overall cumulative L. infantum prevalence of 3.9% was recorded by serology (3.3%) and/or qPCR (0.8%), with a higher rate (10.5%) in southern Italy. The risk of L. infantum infection in cats was significantly associated to the geographical areas (South vs North and Centre; p<0.0001), age class (from 19 months to 6 years old vs ≤18 months old, p = 0.0003), neutering status (not neutered vs neutered, p = 0.0028) and FIV infection (p = 0.0051).Though the role of cats in the epidemiology of L. infantum is still debated, our findings indicate that cats are exposed to and/or infected by this protozoan, mainly in endemic regions of Italy. Hence, a standardization of procedures for a prompt diagnosis of L. infantum infection in cats and for screening cat population is crucial for a better understanding of the epidemiology of feline leishmaniasis, and of the potential role of cats in the transmission cycle of zoonotic visceral leishmaniasis.